Website Accessibility 3 Best Universities in West Sumatra regarding Online Reputation - Adzkia Kirana Dipa; Hanny Hafiar; Agus Rahmat (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
For higher education institutions, reputation is crucial because it has a broad influence. The three best universities in West Sumatra already have PR practitioners using the Internet, especially websites, as a medium of communication that help to shape the reputation. This study aims to evaluate the three websites to see the maximization of resources to ensure easy accessibility to make it easier for audiences to obtain information. This research uses a descriptive quantitative method. The researcher did the evaluation using website evaluation tools, Taw, and aXe analysis tools. Test parameters are based on WCAG 2.0 guidelines. In this study, the researcher has identified several indicators of checking websites that violate the guidelines the most. There are several notes on accessibility problems at a moderate level that must be corrected to increase the level of web access. Then, several parts of the website must be reviewed to be replaced or improved so that they do not have the potential to become an issue on accessibility. After accessibility, privacy protection on websites can also be questioned, so trust in websites will decrease. Website developers must do their best to explain information honestly and responsibly, and interactivity can always be improved.Keywords: Website accessibility, college, online reputation ABSTRAKBagi institusi perguruan tinggi, reputasi menjadi penting karena memiliki pengaruh yang luas. Tiga perguruan tinggi terbaik di Sumatera Barat sudah memiliki praktisi Humas dan telah memanfaatkan internet, khususnya situs web sebagai sarana komunikasi, yang telah membantu membentuk reputasi perguruan tinggi masing-masing. Penelitian ini bertujuan mengevaluasi ketiga situs web untuk melihat pemaksimalan sumber daya untuk menjamin kemudahan aksesibilitas pada situs web untuk memudahkan khalayak memperoleh informasi. Penelitian ini menggunakan metode kuantitatif deskriptif. Peneliti melakukan evalusi menggunakan tools evaluasi situs web yaitu alat analisis Taw dan aXe. Parameter uji didasarkan pada pedoman WCAG 2.0. Peneliti telah mengidentifikasi beberapa indikator pemeriksaan situs web yang paling melanggar pedoman, terdapat beberapa catatan permasalahan aksesibilitas pada tingkatan moderate yang harus diperbaiki untuk meningkatkan tingkat akses web. Kemudian, terdapat 516 kesalahan dalam tingkatan perceivable dan beberapa bagian website yang harus direview ulang untuk diganti atau ditingkatkan agar tidak berpotensi menjadi issue pada aksesibilitas. Selain Aksesibilitas, perlindungan privasi di situs web juga dapat dipertanyakan, jadi kepercayaan pada situs web akan menurun. Pengelola situs web harus melakukan yang terbaik untuk menjelaskan informasi dengan jujur dan bertanggung jawab dan interaktivitas dapat selalu ditingkatkanKata Kunci: Aksesibilitas situs web, perguruan tinggi, reputasi online